Corrupción organizacional: una propuesta de marco teórico - Morales Inga, Sergio (2022)
Different from typical cases of corporate crime, organizational corruption refers to corrupt behavior whose main beneficiary is not the individual but the organization. Through a literature review, this article aims to understand organizational corruption from a scheme that recognizes its main mechanisms (socialization, normalization, and rationalization) and features (linked to elements such as structure, leadership, business ethics, organizational culture, and national culture). By way of contribution, this article proposes a theoretical framework that allows a qualitative understanding of the mechanisms and organizational features that make organizational corruption possible. Likewise, as a purpose, this article indicates that a qualitative understanding will allow the design of anti-corruption policies that recognize its inherent complexity.